2013
DOI: 10.3732/ajb.1200306
|View full text |Cite
|
Sign up to set email alerts
|

Root hydrotropism: An update

Abstract: While water shortage remains the single-most important factor influencing world agriculture, there are very few studies on how plants grow in response to water potential, i.e., hydrotropism. Terrestrial plant roots dwell in the soil, and their ability to grow and explore underground requires many sensors for stimuli such as gravity, humidity gradients, light, mechanical stimulations, temperature, and oxygen. To date, extremely limited information is available on the components of such sensors; however, all of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 97 publications
1
67
0
2
Order By: Relevance
“…In line with this hypothesis, water-stressed roots also contain degraded amyloplasts (Takahashi et al, 2003;Nakayama et al, 2012;Cassab et al, 2013), which may be important for osmotic adjustment and presumably also makes them less responsive to gravity.…”
Section: Growth Direction Is Determined Locally By Water Availabilitymentioning
confidence: 71%
“…In line with this hypothesis, water-stressed roots also contain degraded amyloplasts (Takahashi et al, 2003;Nakayama et al, 2012;Cassab et al, 2013), which may be important for osmotic adjustment and presumably also makes them less responsive to gravity.…”
Section: Growth Direction Is Determined Locally By Water Availabilitymentioning
confidence: 71%
“…For example, plant roots can sense soil moisture gradients and grow toward to a source of water (referred as hydrotropism). 1 Plants also can modify their root system architecture to adapt themselves to the water stress conditions. We have previously shown that plants are able to stimulate lateral root development with enhanced stress tolerance through programmed cell death of the root apical meristem (RAM) of the primary roots under severe water stress.…”
Section: Introductionmentioning
confidence: 99%
“…The root system, which is directly in contact with soil particles, can integrate environmental cues to adjust its development in order to optimize nutrient (Péret et al, 2011;Lynch, 2013) and water uptake (Cassab et al, 2013;Lynch, 2013;Bao et al, 2014) or avoid regions of high salinity (Galvan-Ampudia et al, 2013). Once anchored in the soil, roots must deal with the constraints of their local environment and develop specific barriers to balance uptake of nutrients, water, and interactions with symbionts with protection against detrimental biotic and abiotic factors.…”
mentioning
confidence: 99%